(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The current research aims to identify the effect of using a model of generative learning in the achievement of first-middle students of chemical concepts in science. The researcher adopted the null hypothesis, which is there is no statistically significant difference at the level (0.05) between the mean scores of the experimental group who study using the generative learning model and the average scores of the control group who study using the traditional method in the chemical concepts achievement test. The research consisted of (200) students of the first intermediate at Al-Farqadin Intermediate School for Boys affiliated with the Directorate of General Education in Baghdad Governorate / Al-Karkh 3 with (5) classes (A, B, C, D, E), and two classes (A, D) were chosen by simple random assignment. Class (A) was the control group that was studied in the traditional method; class (D) was the experimental group that was studied using the generative learning model. The research sample was (80) students distributed in two classes each class included (40) Students. The failing students were excluded. The members of the two groups were tested based on the variables of intelligence, and previous achievement in science. To verify the goal of the research, an achievement test for chemical concepts was prepared consisting of (21) objective items with multiple choice, and (4) alternatives. It is formulated according to the minimum levels of Bloom’s classification in the cognitive domains of remembering, comprehension, and application. The experiment was applied in the first semester of the academic year (2019-2020), and it took (4) weeks. The results showed that the members of the experimental group that were taught using the generative learning model outperformed their peers in the control group that was taught by the traditional method with a statistically significant difference in the achievement test of chemical concepts. The research came out with a number of recommendations and suggestions: using the generative learning model for students of the first intermediate students in science.